2005
DOI: 10.1016/s1542-3565(05)00184-9
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is one of the most common diagnoses made by gastroenterologists and primary care providers alike, and yet the underlying mechanism remains poorly understood. Family and twin studies suggest that IBS may have a genetic basis. Several candidate gene association studies have been performed, but thus far, they have failed to clearly identify an "IBS gene." Epidemiological studies are needed to facilitate phenotype definition and identify relevant environment risk factors that will ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 55 publications
1
50
1
2
Order By: Relevance
“…Whilst several candidate genes have been proposed, no study to date has identified an "IBS" gene, although it must be noted that several of the published studies are small and statistically under powered to detect what is probably a small influence (see the review by Saito and Talley 65 ). Large population based, genome wide association studies represent one of the most exciting potential avenues for delineating the genetic factors that contribute to the development of FGID in the future but the prerequisite step is the further definition of the clinical phenotype based on pathophysiological features rather than purely symptom based criteria.…”
Section: Psychological and Genetic Influencesmentioning
confidence: 99%
“…Whilst several candidate genes have been proposed, no study to date has identified an "IBS" gene, although it must be noted that several of the published studies are small and statistically under powered to detect what is probably a small influence (see the review by Saito and Talley 65 ). Large population based, genome wide association studies represent one of the most exciting potential avenues for delineating the genetic factors that contribute to the development of FGID in the future but the prerequisite step is the further definition of the clinical phenotype based on pathophysiological features rather than purely symptom based criteria.…”
Section: Psychological and Genetic Influencesmentioning
confidence: 99%
“…SERT develops before fetal expression of TPH1 or TPH2 is evident, and thus, for mucosal SERT expression to be influenced by serotonin, the source of the serotonin would have to be maternal. IBS does appear to have a familial contribution, although twin studies have shown only a modest contribution of genetics (34). It is thus possible that maternal serotonin can contribute to fetal bowel development and account for a familial transmission that is independent of the genetic makeup of the fetus.…”
Section: Maternal Serotonin May Be a Morphogen-like Signaling Moleculementioning
confidence: 99%
“…One of the most common forms of visceral pain and abdominal discomfort is irritable bowel syndrome (IBS). Several studies have concluded that there is strong genetic component in the incidence of IBS (familial IBS), and many candidate genes have been investigated, although no strong association with any of the candidate genes, such as P2X3 or TRPV1, has been found (66). The observation that families with SCN5A-related cardiac channelopathies report much higher incidence of abdominal pain than a control population has led to the hypothesis that sodium channelopathies may be a contributing cause in the pathogenesis of functional bowel disorders (67).…”
Section: Visceral Painmentioning
confidence: 99%